Delivered from the elements of the world : atonement, justification, mission - Leithart, Peter J. (Downers Grove, Ill. : IVP Academic, an imprint of InterVarsity Press, 2016)
In this wide-ranging study bursting with insights, Peter Leithart explores how and why Jesus' death and resurrection addresses the deepest realities of this world. This biblical and theological examination of atonement and justification challenges conventional perceptions and probes the depths of the death that changes everything.
Atonement as social theory -- Under the elements of the world -- The physics of the old creation -- Among Gentiles: an ancient Jewish travelogue -- Flesh -- What Torah does -- Good news of God's justice -- The justice of God -- The faith of Jesus Christ -- Justification -- Justified by the faith of Jesus -- Justified from the elements -- Contributions to a theology of mission -- In ranks with the spirit -- Outside the Christian era -- Galatian church, Galatian age -- Cur Deus Homo? -- The metaphysics of atonement: natural and supernatural -- Nature, the supernatural and justification -- Atonement by deliverdict: Romans.
Includes index.
Description based on print version record and CIP data provided by publisher.
Includes bibliographical references and indexes.
English.
Master record variable field(s) change: 050
Keywords: Jesus Christ -- Crucifixion; Jesus Christ; Atonement; Justification (Christian theology); Mission of the church; RELIGION -- Christian Theology -- Soteriology; Atonement; Crucifixion of Jesus Christ; Justification (Christian theology); Mission of the church; Christianity; Religion; Philosophy & Religion; Electronic books